Optimalisasi Teknologi Digital untuk Mendukung Daya Saing UMKM di Era Transformasi Digital - Prasetiyo, Eko; Kasih Mayang Gitaurus; Bagus Setyo Cahyono; Mar’atun Koirotul Fiyana; Silvia Nur Khasanah; Muhammad Abdul Malik; Alif Alfian Syafa’at; Ichsan Iqbal Firdaus; Lailis Sofia; Jefi Widiawan; Lia Ananta; Taufika Nururrohmah; Muhammad Ulil Albab; Ahmad Isa Tranjaya (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Digital transformation has become a central issue in strengthening the competitiveness of MSMEs, especially in rural areas. This community service activity focuses on assisting MSMEs in Gunungan Village, Magetan Regency, in facing the challenges of the digital era through the digitization of promotion and sales. The objective of this activity is to enhance the digital literacy of SME operators, expand market reach through social media and digital platforms, and strengthen local identity through location-based digital integration (Google Maps, Google Business Profile). The method employed is a participatory approach based on community organizing, implemented through stages of socialization, technical training, direct mentoring, and participatory evaluation. The results of the activity showed an increase in SMEs' understanding of the importance of digitalization, skills in creating digital business accounts, and the utilization of location features in marketing. The expected social changes also began to emerge, such as increased community involvement in the digital ecosystem, the emergence of collaboration among SMEs, and the formation of a digital SME community in Gunungan Village. This activity underscores the importance of a sustainable and adaptive approach in empowering communities through digital applications